Meta-analysis of HLA-DRB1 and HLA-DQB1 polymorphisms in Latin American patients with systemic lupus erythematosus (2008)
Objective: To estimate the common effect size of HLA-DRB1 and -DQB1 alleles on systemic lupus erythematosus (SLE) susceptibility across Latin America populations through a meta-analysis. Methods: Case-control studies on HLA class II association with SLE in Latin America were searched up to August 2007. The effect summary odds ratios (ORs) and 95% confidence intervals (CIs) were obtained by means of the random effect model. Results: Eleven studies were selected, which included 747 cases and 1180 controls. Associations with SLE susceptibility were found for HLA-DR2 (OR: 1.75; 95% CI: 1.40-2.19) and -DR3 (OR: 2.02; 95% CI: 1.44-2.83) groups. HLA-DRB1*0301 allele disclosed the strongest association (OR: 2.14; 95% CI: 1.28-3.56). HLA-DR3-DQ2 haplotype was a risk factor (OR: 2.92; 95% CI: 1.66-5.14). A protective effect was found for the HLA-DR5 group (OR: 0.43; 95% CI: 0.27-0.67), mainly due to a negative association between HLA-DRB1*1101 allele and disease (OR: 0.21; 95% CI: 0.06-0.72). Functional analysis of susceptibility and protective alleles revealed physicochemical differences of critical amino acids shaping the peptide-binding groove at DR? chain allowing us to infer an approach to understand the role of HLA in SLE. No significant association was established for HLA-DQB1 alleles. Conclusions: HLA-DRB1 gene is a mayor factor for development of SLE in Latin Americans. © 2007 Elsevier B.V. All rights reserved.